2020
DOI: 10.1039/c9ra09380j
|View full text |Cite
|
Sign up to set email alerts
|

An l-cystine/l-cysteine impregnated nanofiltration membrane with the superior performance of an anchoring heavy metal in wastewater

Abstract: Considerable efforts are being made to develop new materials and technologies for the efficient and fast removal of toxic ions in drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Therefore, efficient methods of Hg removal are still being sought, including through the development of membrane techniques. For example, micellar enhanced ultrafiltration (MEUF) with sodium dodecyl sulphate (SDS) using a polyacrylonitrile membrane allows the rejection of Hg up to 96.83% [ 76 ] or with SDS and cetylpyridinium chloride (As, Hg retention 95%) [ 77 ], while the NF process with L-cystine/L-cysteine impregnated with L-cystine/L-cysteine shows very high retention (99.99%) and can effectively reduce the Hg(II) concentration from 10 ppm to 0.18 ppb, thus below the acceptable limits in drinking water (2 ppb) [ 78 ]. Similar results are obtained in the pyrite (FeS 2 )-supported UF process (R ≈ 100%), with adsorption on pyrite and membrane filtration [ 79 ].…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…Therefore, efficient methods of Hg removal are still being sought, including through the development of membrane techniques. For example, micellar enhanced ultrafiltration (MEUF) with sodium dodecyl sulphate (SDS) using a polyacrylonitrile membrane allows the rejection of Hg up to 96.83% [ 76 ] or with SDS and cetylpyridinium chloride (As, Hg retention 95%) [ 77 ], while the NF process with L-cystine/L-cysteine impregnated with L-cystine/L-cysteine shows very high retention (99.99%) and can effectively reduce the Hg(II) concentration from 10 ppm to 0.18 ppb, thus below the acceptable limits in drinking water (2 ppb) [ 78 ]. Similar results are obtained in the pyrite (FeS 2 )-supported UF process (R ≈ 100%), with adsorption on pyrite and membrane filtration [ 79 ].…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…Mitigation of mercury pollution of drinking water can be done by direct treatment of drinking water or treatment of pollution sources such as industrial wastewater streams where Hg concentrations are much higher. The common methods to remove mercury from wastewater are precipitation [ 51 ], cementation [ 4 ], ion exchange [ 52 ], adsorption [ 53 ], nanofiltration [ 54 ], and solvent extraction [ 55 ]. Slow kinetics, low capacities due to heterogeneous reactions and interface transfer are the main limitations of said methods that make development of new techniques for mercury separation interesting [ 56 , 57 ].…”
Section: The Toxicity Of Mercury and Its Removalmentioning
confidence: 99%
“…Moreover, addition of chlorine-, iodine- and sulfur-treated activated carbon boost its capacity to capture elemental mercury [ 59 ], and the efficiency of mercury removal can also be enhanced by increasing the oxygen concentration [ 60 ]. Zhang et al [ 54 ] reported that a sulfur-functionalized polyamide-based nanofiltration membrane can effectively reduce Hg 2+ concentrations in drinking water sample from 10 ppm to a low level of 0.18 ppb where the acceptable limit of Hg in drinking water is around 2 ppb. Single metals can also be used to adsorb mercury.…”
Section: The Toxicity Of Mercury and Its Removalmentioning
confidence: 99%
“…However, acid–base reaction was not observed in the presence of water, judging from the absence of oxonium ion (H 3 O + ). Previous research on the ab initio statics and dynamics showed that hydroxide or hydroxyl radical is the main culprit of degradation and induced the instant hydrogen abstract from the protic cations (e.g., MA), consequently producing the degradation product of gaseous methylamine . Similarly, it could be expected that the proton of BA is instantly transferred to the unstable radical and/or hydroxide from the molecular arrangement shown in Figure c.…”
mentioning
confidence: 91%
“…As an approach to theoretically study the functionalized perovskite surfaces with small molecules, density functional theory (DFT) calculations inspired by the work of Yang et al were performed. Although many surfaces in perovskites could be expected depending on the type of termination, defect, and/or orientation, current study adopted the (100) MAPbI 3 surface which has been suggested to be stable than other surfaces. Figure a shows the optimized structures of the functionalized surfaces of MAPbI 3 with additives.…”
mentioning
confidence: 99%